2007
DOI: 10.1021/la063105+
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Anion Channel Transports Calcium Ions through Biomimetic Membranes

Abstract: The mitochondrial outer membrane channel (VDAC), a central player in mitochondria and cell death, was reconstituted in polymer-supported phospholipid bilayers. Highly purified VDAC was first reconstituted in vesicles; channel properties and NADH-ferricyanide reductase activity were ascertained before deposition onto solid substrates. 1-Palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine/1,2-distearoyl-sn-glycero-3-phosphoethanolamine-poly(ethylene glycol)-N-hydroxysuccinimide mixed vesicles containing VDAC were lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 59 publications
0
34
0
Order By: Relevance
“…134 At a more integrated level, mitochondria are interconnected within the so-called mitochondrial network, undergo fusion and fission events to adapt to stress, 135 and communicate with other organelles such as the endoplasmic/sarcoplasmic reticulum via microdomains to transfer Ca 2+ and trigger some proapoptotic signaling cascade in case of stress. 63,[136][137][138] For instance, in the heart, a partial loss of optic atrophy type 1 (OPA1), an IM protein involved in mitochondrial fusion, affects the mitochondrial network morphology, PTP sensitivity to Ca 2+ , and cardiac adaptation to pressure overload. 139 But the links among mitochondrial dynamics, PTP, and pathology remain largely unknown and have to be further explored.…”
Section: 114mentioning
confidence: 99%
“…134 At a more integrated level, mitochondria are interconnected within the so-called mitochondrial network, undergo fusion and fission events to adapt to stress, 135 and communicate with other organelles such as the endoplasmic/sarcoplasmic reticulum via microdomains to transfer Ca 2+ and trigger some proapoptotic signaling cascade in case of stress. 63,[136][137][138] For instance, in the heart, a partial loss of optic atrophy type 1 (OPA1), an IM protein involved in mitochondrial fusion, affects the mitochondrial network morphology, PTP sensitivity to Ca 2+ , and cardiac adaptation to pressure overload. 139 But the links among mitochondrial dynamics, PTP, and pathology remain largely unknown and have to be further explored.…”
Section: 114mentioning
confidence: 99%
“…An easier and proven way to ensure that the microcapsules do not stimulate an immune response is coating the polyelectrolyte with phospholipid membranes. [4][5][6][7][8] A further advantage of this approach is the possibility to incorporate biomolecules such as membrane transport proteins in the supported phospholipid membranes, as has been explored recently by several groups [9,10] and reported in this paper. The…”
Section: Introductionmentioning
confidence: 96%
“…In this respect, electrode-supported bilayer lipid membranes (BLMs) represent ideal model systems as they allow embedment of the protein within the membrane and the generation of a transmembrane potential. Reconstitution of the VDAC in BLMs has in fact already been demonstrated, 23 but such devices have not yet been coupled to in situ IR spectroscopic measurements. Recently, we demonstrated that the construction of a tethered bilayer lipid membrane (tBLM) on nanostructured Au film electrodes meets the requirements for potential-controlled IR spectroscopy since the metallic support allows for applying surface-enhanced infrared absorption (SEIRA) spectroscopy.…”
Section: Introductionmentioning
confidence: 99%